2006
DOI: 10.1097/00005131-200603000-00002
|View full text |Cite
|
Sign up to set email alerts
|

The Olecranon Osteotomy: A Six-year Experience in the Treatment of Intraarticular Fractures of the Distal Humerus

Abstract: In this study, no osteotomy nonunions were encountered in 67 patients, more than half of which were open injuries. Regardless of which type of fixation is used to secure the osteotomy, secure stabilization must be obtained. Isolated symptomatic olecranon fixation requiring removal occurred in approximately 8% of patients. Although not necessary for all fractures of the distal humerus, the olecranon osteotomy can be useful in the visualization of the complex articular injuries, allowing accurate articular reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
105
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(113 citation statements)
references
References 33 publications
3
105
1
4
Order By: Relevance
“…[16,17,25] Olecranon osteotomy has been associated with a number complications, including delayed union [14] and 0% to 10% risk of nonunion. [8,27] It was suggested that union problems observed in olecranon osteotomies are mostly related to the transverse osteotomy technique (30%). [28] Chevron shaped osteotomy reduced these complication.…”
Section: Discussionmentioning
confidence: 99%
“…[16,17,25] Olecranon osteotomy has been associated with a number complications, including delayed union [14] and 0% to 10% risk of nonunion. [8,27] It was suggested that union problems observed in olecranon osteotomies are mostly related to the transverse osteotomy technique (30%). [28] Chevron shaped osteotomy reduced these complication.…”
Section: Discussionmentioning
confidence: 99%
“…11 Other level IV series of patients treated with olecranon osteotomy have reported rates of hardware removal ranging from 6% to 30% and nonunion of the olecranon osteotomy in 0-9% of patients. [14][15][16][17][18] One level III study compared the two approaches for the fixation of Question 1: What is the value of preoperative CT scanning in the assessment of distal humerus fractures?…”
Section: Resultsmentioning
confidence: 99%
“…The muscle power of triceps was almost equal to that of opposite limb in young patients. Sixty one patients with olecranon osteotomy for distal humerus fractures were followed up for six years by Coles CP et al [12] . They found adequate articular reduction of humerus in all the cases.…”
Section: Discussionmentioning
confidence: 99%